2014
DOI: 10.1016/j.visres.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the accommodation-vergence conflict on vergence eye movements

Abstract: With the broader use of stereoscopic displays, a flurry of research activity about the accommodation-vergence conflict has emerged to highlight the implications for the human visual system. In stereoscopic displays, the introduction of binocular disparities requires the eyes to make vergence movements. In this study, we examined vergence dynamics with regard to the conflict between the stimulus-to-accommodation and the stimulus-to-vergence. In a first experiment, we evaluated the immediate effect of the confli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…However, while the latency of vergence eye movements was not significantly different between refractive groups, the time constant of the vergence response in myopic observers was significantly slower than in emmetropes. Our observations are consistent with Vienne et al (2014) who found that vergence responses were slower with conflicting disparity and blur cues, as well as with Semmlow and Wetzel (1979) who showed that binocular vergence movements are faster when disparity and blur are both available than when only disparity specifies a change in distance. Thus, slower vergence movements in myopes are consistent with the previous finding that myopes make less use of retinal defocus information (Cufflin et al, 2007; Rosenfield and Abraham-Cohen, 1999) and extends this observation from the perceptual to the oculomotor system.…”
Section: Discussionsupporting
confidence: 92%
“…However, while the latency of vergence eye movements was not significantly different between refractive groups, the time constant of the vergence response in myopic observers was significantly slower than in emmetropes. Our observations are consistent with Vienne et al (2014) who found that vergence responses were slower with conflicting disparity and blur cues, as well as with Semmlow and Wetzel (1979) who showed that binocular vergence movements are faster when disparity and blur are both available than when only disparity specifies a change in distance. Thus, slower vergence movements in myopes are consistent with the previous finding that myopes make less use of retinal defocus information (Cufflin et al, 2007; Rosenfield and Abraham-Cohen, 1999) and extends this observation from the perceptual to the oculomotor system.…”
Section: Discussionsupporting
confidence: 92%
“…However, in VR, the focal distance of all objects on the screen is constant, and the eyes must converge without changing accommodation to maintain a clear retinal image. Thus, wearing a VR HMD creates a dissociation between convergence and accommodative demands 1 , which may contribute to visual discomfort 2 4 . Whether the effects of this disassociation persist after HMD use is unknown 5 , but a study investigating the effect of an early VR HMD system found a shift towards esophoria, and an extended near point of binocular convergence shortly after a 10-minute VR exposure 6 .…”
Section: Introductionmentioning
confidence: 99%
“…One way to overcome this cross-dependence is to employ a cue conflict paradigm in which the vergence distance and the accommodation distance are set to different values. Using such a conflict paradigm, Vienne et al (2014) revealed that vergence was significantly affected by the absence of blur cues; responses were slower with longer latency. The authors also found that the accommodation-vergence conflict had more impact on divergence latency than convergence latency.…”
Section: Introductionmentioning
confidence: 99%